The effectiveness of acute normolvolemic hemodilution and autologous prime on intraoperative blood management during cardiac surgery. (September 2017) - Stammers, Alfred H.; Mongero, Linda B.; Tesdahl, Eric; Stasko, Andrew; Weinstein, Samuel
Objective: Intraoperative blood management during cardiac surgery is a multifaceted process incorporating various interventions directed at optimizing oxygen delivery and enhancing hemostasis. The purpose of this study was to evaluate the effects of acute normovolemic hemodilution (ANH) and autologous priming (AP) on preserving the hematocrit during cardiopulmonary bypass (CPB). Method: Case records from a national registry of adult patients who underwent cardiac surgery between January and October 2016 were reviewed. Groups were determined as follows: ANH, AP, ANH+AP or Neither. Primary endpoint was first the hematocrit on CPB with secondary endpoints of hematocrit drift and red blood cell (RBC) transfusion rate. Results: Eighteen thousand and twenty-four (18, 024) consecutive patients were reviewed. The first CPB hematocrit was lowest in the ANH group (26.5%±4.4%) and highest in ANH+AP patients (27.5%±4.8%) (p<0.001). The change in hematocrit was greatest in the ANH group (8.3%±3.9%) compared to both the AP (6.4%±3.8%) and ANH+AP (6.9%±4.1%) groups (p<0.001). Intraoperative RBC transfusions were as follows: ANH 26 (7.8%), AP 2, 531 (20.0%), ANH+AP 287 (10.3%) and Neither 592 (26.7%) (p<0.001). Conclusions: Regression results show that the use of ANH will result in the greatest decline in hematocrit values. When combined with AP, higher hematocrits and lower transfusions were seen.